Cognitive–behavioural therapies and exercise programmes for patients with fibromyalgia: state of the art and future directions. Issue 5 (17th August 2006) - van Koulil, S; Effting, M; Kraaimaat, F W; van Lankveld, W; van Helmond, T; Cats, H; van Riel, P L C M; de Jong, A J L; Haverman, J F; Evers, A W M
Abstract : This review provides an overview of the effects of non-pharmacological treatments for patients with fibromyalgia (FM), including cognitive–behavioural therapy, exercise training programmes, or a combination of the two. After summarising and discussing preliminary evidence of the rationale of non-pharmacological treatment in patients with FM, we reviewed randomised, controlled trials for possible predictors of the success of treatment such as patient and treatment characteristics. In spite of support for their suitability in FM, the effects of non-pharmacological interventions are limited and positive outcomes largely disappear in the long term. However, within the various populations with FM, treatment outcomes showed considerable individual variations. In particular, specific subgroups of patients characterised by relatively high levels of psychological distress seem to benefit most from non-pharmacological interventions. Preliminary evidence of retrospective treatment analyses suggests that the efficacy may be enhanced by offering tailored treatment approaches at an early stage to patients who are at risk of developing chronic physical and psychological impairments.